Structure and composition of natural holm oaks in the Slate Altitude from Viñales Municipality, Pinar del Río, Cuba - González-Menéndez, Modesto; Alonso-Torrens, Yatsunaris; Urrutia-Hernández, Isyoel; Miñoso, Yaumara; Santana, Isabel; Luis-Suárez, Jesús; González-Torres, Carlos Manuel (Instituto de Ecología, A.C., 2019)
The investigation was carried out in the holm oaks in the Slate Altitude in the Agroforestry La Palma and in the Agroforestry Experimental Station of Viñales Municipality, with the objective to determine the structure and composition of natural oaks. Two different places were layed out regarding a level of man intervention. There were established 10 square plots (100 m2), five in each of the included in the areas in the study, in way simple aleatoia. Alpha and beta diversity was determined; the horizontal structure was evaluated by calculating the index of ecological importance and the distribution by diameter classes. Also, it was described the vertical structure through the richness of species in each stratum as well as its sociological position. The richness of the species proved a high floristic diversity associated to the oaks. There were identified 38 species associated to the oaks, grouped in 25 families, where the Melastomataceae family with four species and Fabaceae, Rubiaceae and Sapindaceae with three species is the most represented. It was proved that the silvicola management and pastoral of the pig livestock level had strong influence in the structure and composition of the natural oaks. It was determined that the Quercus cubano A. Rich.  As dominant specie with the most ecological importance in this formation, it has irregular presence in the structure of this forest, turning to be vulnerable to natural disturbances potential human intervention, showing a weak competitive skill. The obtained results constitute a reference for the management of this endemic specie in the west of Cuba.